ByzRev 03.2021.031: Sabine Feist (Hrsg.), Transforming Sacred Spaces: New Approaches to Byzantine Ecclesiastical Architecture from the Transitional Period: (Spätantike – Frühes Christentum – Byzanz. Kunst im ersten Jahrtausend. Reihe B: Studien und Perspektiven 48). Wiesbaden: Reichert Verlag 2020. - Fingarova, Galina (The Byzantine Review, 2021)
Sabine Feist (Hrsg.), Transforming Sacred Spaces: New Approaches to Byzantine Ecclesiastical Architecture from the Transitional Period (Spätantike – Frühes Christentum – Byzanz. Kunst im ersten Jahrtausend. Reihe B: Studien und Perspektiven 48). Wiesbaden: Reichert Verlag 2020. 267 S., 115 s/w Abb. – ISBN: 978-3-954-90419-8 (€ 98.00)